2023
DOI: 10.3389/fonc.2022.1073672
|View full text |Cite
|
Sign up to set email alerts
|

Role of Notch2 pathway in mature B cell malignancies

Abstract: In recent decades, the Notch pathway has been characterized as a key regulatory signaling of cell-fate decisions evolutionarily conserved in many organisms and different tissues during lifespan. At the same time, many studies suggest a link between alterations of this signaling and tumor genesis or progression. In lymphopoiesis, the Notch pathway plays a fundamental role in the correct differentiation of T and B cells, but its deregulated activity leads to leukemic onset and evolution. Notch and its ligands De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 128 publications
0
5
0
Order By: Relevance
“…Bone marrow transplantation of irradiated mice with recombinant ADAM10 revealed that the lymph nodes of the transplanted mice had normal lymphoid structure and the MZB in the cortical area were restored to normal (143). The study demonstrated that Notch-mediated ADAM10 expression restored secondary lymphoid structures and promoted the neogenesis of splenic germinal centers in irradiated mice (84,144). In the spleen, the Notch2 ligand (delta-like 1, DL1) is present at high concentrations in the small splenic veins which is considered a key activator of MZB development (82, 84).…”
Section: Regulation Of Irradiated-b Cells By Notch Signalingmentioning
confidence: 91%
See 3 more Smart Citations
“…Bone marrow transplantation of irradiated mice with recombinant ADAM10 revealed that the lymph nodes of the transplanted mice had normal lymphoid structure and the MZB in the cortical area were restored to normal (143). The study demonstrated that Notch-mediated ADAM10 expression restored secondary lymphoid structures and promoted the neogenesis of splenic germinal centers in irradiated mice (84,144). In the spleen, the Notch2 ligand (delta-like 1, DL1) is present at high concentrations in the small splenic veins which is considered a key activator of MZB development (82, 84).…”
Section: Regulation Of Irradiated-b Cells By Notch Signalingmentioning
confidence: 91%
“…Indeed, a commitment of HSPCs into the B lineage needs to inhibit the Notch1 signal (163). For instance, when Pro-B cells undergo maturation in the BM, bone marrow stromal cells secrete the cytokine CXCL12, which effectively suppresses the expression of Notch ligands (144). With the Pro-B cells continuing to develop, Notch signaling plays an increasingly important role in subsequent developmental processes (134).…”
Section: Regulation Of Irradiated-b Cells By Notch Signalingmentioning
confidence: 99%
See 2 more Smart Citations
“…The top 10 proteins which were significantly up-regulated in HEPM-EXO showed a high intercorrelation and were reported to be associated with cell growth, cell communication and signal transduction. [25][26][27][28][29][30][31][32][33][34] HEPM-EXO may rely on some of these proteins to regulate the proliferation and migration of HIOEC. Among these proteins, THBS1 was frequently associated with exosomal regulation of cell migration.…”
mentioning
confidence: 99%